Keberadaan Bakteri Eschericia Coli dan Coliform pada Sumur Gali dan Bor Rumah Pemotongan Hewan - Meisura Marlinda; Anita Dewi Moelyaningrum; Ellyke Ellyke (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: The Coliform and Escherichia coli in Dug Well Water and Artesian Well. The quality of well water is related to public health problems. One of the causes of contaminated well water due to contamination by microorganisms, such as Coliform and E. coli bacteria. The quality of well water that is potentially polluted is one of the wells dug at the Slaughterhouse. The purpose of this study was to describe the factors related to the presence of Coliform and E. coli bacteria in wells dug in RPH in Jember Regency. This research is a descriptive research. Data collection techniques are carried out by observation, interviews, measurements, and laboratory tests. Interviews were conducted with the managers of each RPH. Laboratory test results showed that 42% of positive well water contained Coliform bacteria and 75% E. coli bacteria. The construction of dug wells mostly does not meet the physical requirements of wells, the septic tanks do not meet the requirements because some slaughterhouses do not have septic tanks and distances of less than 11 meters, the latrines are mostly in good condition, the SPAL of Jember Regency is mostly in the condition is good, most of the groundwater level in RPH wells in Kabupaten Jember has a height of 1 to 5 meters, all types of soil in RP Jember Regency are of sand soil type, and rainfall is relatively high. The dugs wells contruction and the latrines should be reconstruction to meet the requirement of clean water for increase the public health.